Sistem Informasi Posyandu ABC Desa Cit Terhadap Peningkatan Pelayanan Kesehatan Ibu dan Anak - Probonegoro, Wishnu Aribowo; Sari, Lili Indah (Universitas Multi Data Palembang, 2025)
Posyandu is a basic health service for people in villages in Indonesia, but posyandu focuses more on babies, toddlers, mothers, especially pregnant and breastfeeding mothers, where services are usually carried out every month. Posyandu abc services in Cit village are still very simple and still manual, starting from registration, data recording, examination, immunization and reports made, all of which are still done manually, so that the services provided are slow and less than optimal, long queues and limited officers at the posyandu. Errors in the data recording process also often occur. The problems that occurred at the posyandu abc in Cit village attracted the author to conduct research and help provide solutions by creating a posyandu information system that can be used, in order to facilitate and smooth services for mothers and children. In this study, the author used a qualitative descriptive method and the Waterfall method as a method for developing the system in order to support this research. It is hoped that with the existence of the posyandu abc information system in Cit village, data processing, the registration process for maternal and child health services can be faster, measurable, effective and efficient. Facilitates data storage and access